2016
DOI: 10.1037/xlm0000270
|View full text |Cite
|
Sign up to set email alerts
|

Incidental learning of trust: Examining the role of emotion and visuomotor fluency.

Abstract: Eye gaze is a powerful directional cue that automatically evokes joint attention states. Even when faces are ignored, there is incidental learning of the reliability of the gaze cueing of another person, such that people who look away from targets are judged less trustworthy. In a series of experiments, we demonstrated further properties of the incidental learning of trust from gaze direction. First, the emotion of the face, whether neutral or smiling, influenced the pattern of trust learning. Second, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 36 publications
4
25
0
1
Order By: Relevance
“…Thus, what kind of information indicating relative status would influence face-based perceived trustworthiness, and whether it is modulated by people’s stereotypes, are further questions to be answered. Additionally, though sample sizes in the current studies were decided on the basis of similar research on social judgments of face ( Rogers et al, 2014 ; Manssuer et al, 2016 ; Strachan et al, 2016 , 2017 ; Sofer et al, 2017 ; Strachan and Tipper, 2017 ), the sample size was lower than the recommendations of Fraley and Vazire’s study ( Fraley and Vazire, 2014 ). Future research with a larger sample size might be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, what kind of information indicating relative status would influence face-based perceived trustworthiness, and whether it is modulated by people’s stereotypes, are further questions to be answered. Additionally, though sample sizes in the current studies were decided on the basis of similar research on social judgments of face ( Rogers et al, 2014 ; Manssuer et al, 2016 ; Strachan et al, 2016 , 2017 ; Sofer et al, 2017 ; Strachan and Tipper, 2017 ), the sample size was lower than the recommendations of Fraley and Vazire’s study ( Fraley and Vazire, 2014 ). Future research with a larger sample size might be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also shown that the pattern of trust learning can be influenced by incidental learning from facial expression, eye gaze, and so on. (e.g., Reference [51]). De Melo et al [44] found that participants were sensitive to the emotions displayed by the two agents: they cooperated more with the cooperative agent than with the individual one.…”
Section: Black-hat/white-hat Effectmentioning
confidence: 99%
“…They demonstrated that the motion fluency influenced object liking while the objects were assessed while moving, but there were no effects when the objects were subsequently assessed while stationary. Hence there appeared to be little associative learning between the consistent pairing of object-identity and its motion (see also Strachan et al [21] for similar findings in judgements of face trustworthiness). These are important boundary conditions that might limit the utilization of perceptual fluency to applied issues of preference and choice, and hence they require further research.…”
Section: Perceptual Fluencymentioning
confidence: 96%